Amplatzer Amulet™ left atrial appendage occluder: A step‐by‐step guide to device implantation. (28th February 2022) - Ellis, Christopher R.
Abstract: Recently receiving Food and Drug Administration approval, the Amplatzer Amulet™ left atrial appendage occluder device (Abbott Medical Inc.) provides a dual seal mechanism alternative to the commercially available Watchman FLX or Watchman 2.5 device for embolic stroke prevention in patients with nonvalvular atrial fibrillation. This step‐by‐step review will cover patient selection, preprocedure imaging assessment, device sizing, device preparation, implant target position assessment, implant technique and troubleshooting, and immediate postimplant follow‐up.